2012
DOI: 10.1002/ajmg.a.35328
|View full text |Cite
|
Sign up to set email alerts
|

Informed consent for whole genome sequencing: A qualitative analysis of participant expectations and perceptions of risks, benefits, and harms

Abstract: Scientific evidence on the extent to which ethical concerns about privacy, confidentiality, and return of results for whole genome sequencing (WGS) are effectively conveyed by informed consent (IC) is lacking. The aim of this study was to learn, via qualitative interviews, about participant expectations and perceptions of risks, benefits, and harms of WGS. Participants in two families with Miller syndrome consented for WGS were interviewed about their experiences of the IC process and their perceptions of risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
114
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(120 citation statements)
references
References 18 publications
6
114
0
Order By: Relevance
“…Our results echo other studies that have found attitudes towards personal data sharing in research to be more complex than this, influenced by contextual factors and trust in research institutions. 16,17 Our findings reinforce that when researchers are trusted, many participants do not mind contributing identifiable personal data to multiple research projects provided that they are kept informed, to some extent, about the nature of the research they are contributing to [18][19][20] and that personal data sharing is undertaken more willingly by those who believe that research will yield concrete benefits, either for themselves, society, or both. [19][20][21] We have shown that concerns about personal data sharing are not fully addressed by focusing on the magnitude of the risk of an anonymity breech, and that views about confidentiality have plural origins.…”
Section: Discussionsupporting
confidence: 57%
“…Our results echo other studies that have found attitudes towards personal data sharing in research to be more complex than this, influenced by contextual factors and trust in research institutions. 16,17 Our findings reinforce that when researchers are trusted, many participants do not mind contributing identifiable personal data to multiple research projects provided that they are kept informed, to some extent, about the nature of the research they are contributing to [18][19][20] and that personal data sharing is undertaken more willingly by those who believe that research will yield concrete benefits, either for themselves, society, or both. [19][20][21] We have shown that concerns about personal data sharing are not fully addressed by focusing on the magnitude of the risk of an anonymity breech, and that views about confidentiality have plural origins.…”
Section: Discussionsupporting
confidence: 57%
“…Despite positive attitudes towards data sharing, [40][41][42]49 most respondents in quantitative as well as in qualitative studies stressed the importance of being informed about data-sharing practices and privacy protection measures during the informed consent process. 30,[39][40][41][42][43] In several studies, Table 1 Informed consent requirements in biobank-based genomic research: main findings…”
Section: Content Analysis Of Articles Includedmentioning
confidence: 99%
“…33,36,[39][40][41][42] Regarding concerns and potential risks of biobank-based genomic research and associated data sharing, in several quantitative and qualitative studies, the three groups (patients, the public and professionals) expressed different views ranging from no concerns to raising concerns pertaining to insurance, employment, access to medical care, the disclosure of genomic information about ethnic heritage and stigmatization. 22,24,36,38,40,[42][43][44][45] In two qualitative studies, patients assigned higher priority to the benefit of data sharing for science and society than to potential risks. 40,43 Similar findings were reported in quantitative studies with the public.…”
Section: Content Analysis Of Articles Includedmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Tabor et al 22,23 on the informed consent process in research WGS found that, although all family members involved wanted to receive results related to the condition for which they were being tested, they differed on their desire to receive incidental findings, even among members of the same family. Several participants also felt that it was important to be able to change their preferences between the time of consent and the time of receiving results.…”
Section: Decision Making and Insurance Considerationsmentioning
confidence: 99%